Pengaruh Penyuluhan HIV/AIDS terhadap Pengetahuan Remaja: Studi Kuasi-Eksperimen di SMA XX di Jakarta Tahun 2025 - Trimawartinah Trimawartinah; Viola Alfiorelia (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
HIV/AIDS remains a significant global health issue, particularly affecting adolescents who are vulnerable to risky behaviours due to limited accurate knowledge. This study aimed to analyse the differences in adolescents’ knowledge about HIV/AIDS before and after a health education intervention at SMAN xx West Jakarta in 2025. A quasi-experimental design with a one-group pre-test–post-test approach was employed. The study was conducted from February to March 2025, involving 100 students selected through non-random sampling. Data were collected using a digital questionnaire via Google Forms, covering topics on diagnosis, symptoms, transmission, and prevention of HIV/AIDS. Data analysis was performed using univariate (frequency and percentage) and bivariate analysis with a paired t-test. The results showed that prior to the intervention, most respondents had a moderate level of knowledge, but misconceptions persisted, particularly regarding modes of transmission and prevention. After the health education session, the mean knowledge score increased significantly (p < 0.05), indicating the effectiveness of the intervention in enhancing students’ understanding. Age, gender, and parental education were found to influence the level of knowledge. These findings highlight the importance of regular HIV/AIDS education programs in schools to strengthen adolescents’ health literacy, reduce stigma toward people living with HIV/AIDS, and prevent risky behaviours.